2008
DOI: 10.1093/annonc/mdm557
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-dependent cell signaling and apoptosis in BRCA1-blocked BG1 ovarian cancer cells in response to plumbagin and other chemotherapeutic agents

Abstract: Taken together, this study indicates that plumbagin has chemotherapeutic potential in BRCA1-mutated/defective ER-positive cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 22 publications
2
65
0
Order By: Relevance
“…It has furthermore been shown to exert anti-proliferation influence in diverse cancer cell lines, both in vivo and in vitro, such as leukemia (Xu et al, 2010), prostate (Aziz et al, 2008;Powolny et al, 2008), breast Ahmad et al, 2008), ovarian (Thasni et al, 2008), cervical (Srinivas et al, 2004;Nair et al, 2008) and melanoma examples.…”
Section: Research Articlementioning
confidence: 99%
“…It has furthermore been shown to exert anti-proliferation influence in diverse cancer cell lines, both in vivo and in vitro, such as leukemia (Xu et al, 2010), prostate (Aziz et al, 2008;Powolny et al, 2008), breast Ahmad et al, 2008), ovarian (Thasni et al, 2008), cervical (Srinivas et al, 2004;Nair et al, 2008) and melanoma examples.…”
Section: Research Articlementioning
confidence: 99%
“…In a study to evaluate the differential ability of selected compounds to inhibit cell growth in relation to BRCA1 (breast cancer 1, early onset) status in ER-positive ovarian cancer cells (Thasni et al 2008), plumbagin was found to be the most effective inducer of apoptosis through its binding to and modulation of ER-alpha in BRCA1 silenced cells. In an earlier study, the effect of tamoxifen, emodin, and plumbagin was analyzed in BRCA1-silenced ovarian cancer cells that express ER (Srinivas et al 2004a).…”
Section: Other Cancersmentioning
confidence: 99%
“…It has been shown that PL has anticarcinogenic and cytotoxic affects on animal models and various cancer cells [16,[19][20][21][22]. It has furthermore been shown to exert antiproliferation influence in diverse cancer cell lines, both in vivo and in vitro [18], such as leukemia [23], prostate [17,24], breast [20,25], ovarian [26], lung [21] and melanoma [27] examples. Sinha and his colleagues carried out in vivo studies on ovarian cancer cells and they concluded that PL is a promising antiangiogenic drug [28].…”
Section: Introductionmentioning
confidence: 99%